2022
DOI: 10.1007/s12155-022-10408-2
|View full text |Cite
|
Sign up to set email alerts
|

Miscanthus Sinensis is as Efficient as Miscanthus × Giganteus for Nitrogen Recycling in spite of Smaller Nitrogen Fluxes

Abstract: Nitrogen (N) recycling is a key mechanism to ensure the sustainability of miscanthus production with no or small fertiliser inputs, but little is known on the subject in miscanthus species other than the most cultivated Miscanthus × giganteus. This field experiment on Miscanthus × giganteus and Miscanthus sinensis quantified plant biomass and N stock dynamics during two years. Endogenous net N fluxes, calculated by the difference in plant N content throughout time, were higher in Miscanthus × giganteus than in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Even when soil VWC dropped by ~4-fold under the shelters, and A net decreased by up to ~26%. Other studies have found a stronger negative leaf photosynthesis response to water deficit ( Barney et al., 2009 ; Lovell et al., 2016 ; Taylor et al., 2016 ; Hawkes and Kiniry, 2018 ; Chen et al., 2020 ), including across 49 switchgrass genotypes in which decreased by 40 – 80% under drought stress ( Liu et al., 2015 ). This discrepancy may be because the control treatment in our field experiment (i.e., plants outside the shelter) experienced ambient environmental conditions, while other studies used irrigated plants as the control.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even when soil VWC dropped by ~4-fold under the shelters, and A net decreased by up to ~26%. Other studies have found a stronger negative leaf photosynthesis response to water deficit ( Barney et al., 2009 ; Lovell et al., 2016 ; Taylor et al., 2016 ; Hawkes and Kiniry, 2018 ; Chen et al., 2020 ), including across 49 switchgrass genotypes in which decreased by 40 – 80% under drought stress ( Liu et al., 2015 ). This discrepancy may be because the control treatment in our field experiment (i.e., plants outside the shelter) experienced ambient environmental conditions, while other studies used irrigated plants as the control.…”
Section: Discussionmentioning
confidence: 97%
“…Few studies reporting changes in leaf carbohydrate under drought conditions in switchgrass suggest that the response may be specific to the particular storage carbohydrate. Key carbohydrates such as trehalose, fructose ( Liu et al., 2015 ), and proline ( Kim et al., 2016 ; Hoover et al., 2018 ) seem to be more readily affected, while other soluble sugars such as glucose or sucrose as well as starch remain relatively constant ( Hoover et al., 2018 ). Our work is distinct from earlier water deficit studies because we present diurnal and seasonal leaf carbohydrate measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, older plants have larger root systems with which to mine soil N, and larger N pools that can be transferred to new buds to support initial growth in early spring. Spring N mobilization ranges between 23 kg ha −1 and 98 kg ha −1 have been reported ( Leroy et al , 2022 ), and these could be help mitigate the size-dependent N limitation, but little is known about the effects of N reserves on leaf N content over years. It is also possible that lower photosynthetic rates result from older plants allocating a larger proportion of N to non-photosynthetic functions as they age, but that is also poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The yield response to N application in Urbana is likely a result of the age of the stand and the concomitant N depletion during the preexperiment years (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) when no N was applied. Although miscanthus can effectively recycle N (Christian et al, 2006;Dierking et al, 2017;Dohleman et al, 2012;Leroy et al, 2022), biomass harvesting can deplete the soil and rhizome N; thus, additional fertilization is required to compensate for the loss (Kantola et al, 2022;Tejera et al, 2021). The different N responses in Pesotum can be attributed to differences in soil conditions compared with Urbana and/or differences in historical N management.…”
Section: Biomass Yield Response To Nmentioning
confidence: 99%